Diagnosis and classification of non‐alcoholic fatty liver disease and non‐alcoholic steatohepatitis: Current concepts and remaining challenges. Issue 1 (20th May 2014) - Hashimoto, Etsuko; Tokushige, Katsutoshi; Ludwig, Jurgen
<x xml:space="preserve">Abstract</x> The high prevalence of non‐alcoholic fatty liver disease (NAFLD) has made the condition an important public health issue. Two clinical entities are manifestations of NAFLD, namely, non‐alcoholic fatty liver (NAFL) and non‐alcoholic steatohepatitis (NASH). The former tends to be benign and non‐progressive while the latter can progress to cirrhosis, which in rare cases gives rise to hepatocellular carcinoma. The diagnosis of NAFLD is based on: (i) a history of no or limited daily alcohol intake (<20 g for women and <30 g for men); (ii) presence of hepatic steatosis by imaging or by histology; and (iii) exclusion of other liver diseases. NAFL is defined histologically by the presence of bland, primarily macrovesicular, hepatocellular fatty change, while NASH features fatty change with inflammation and evidence of hepatocyte injury, such as ballooning degeneration. Presence of fibrosis is a sign of chronicity. Thus, the diagnosis of NAFL/NASH rests on clinicopathological criteria; it always requires both clinical and biopsy‐based information. NAFLD could be both the result and the cause of metabolic syndrome, with a vicious cycle operating between these conditions. Remaining challenges are: (i) the lack of a clear threshold alcohol intake for defining "non‐alcoholic"; (ii) a lacking consensus for the classification of fatty liver disease; and (iii) absence of a histological definition of NASH, which currently remains the gold standard for the diagnosis. Further challenges include the overlap of the criteria for NAFLD and alcoholic liver disease as many obese individuals also consume considerable volumes of alcohol.